Cochlear connexin 30 homomeric and heteromeric channels exhibit distinct assembly mechanisms. (February 2019) - Defourny, Jean; Thelen, Nicolas; Thiry, Marc
Abstract: Many of the mutations in GJB2 and GJB6, which encode connexins 26 and 30 (Cx26 and Cx30), impair the formation of membrane channels and cause autosomal syndromic and non-syndromic hearing loss. In cochlear non-sensory supporting cells, Cx26 and Cx30 form two types of homomeric and heteromeric gap junctions. The biogenesis processes of these channels occurring in situ remain largely unknown. Here we show that Cx30 homomeric and Cx26/Cx30 heteromeric gap junctions exhibit distinct assembly mechanisms in the cochlea. When expressed as homomeric channels, Cx30 preferentially interacts with β-actin in the peripheral non-junctional membrane region, called perinexus, and strongly relies on the actin network for gap junction plaque assembly. In contrast, we found that Cx26/Cx30 heteromeric gap junction plaques are devoid of perinexus and associated actin network, and resist to actin-depolymerizating drug. This supports that Cx26/Cx30 oligomers could be directly delivered from the interior of the cell to the junctional plaque. Altogether, our data provide a novel insight in homomeric and heteromeric gap junction plaque assembly in the cochlea. Graphical abstract: Unlabelled Image Highlights: Cx30 and Cx26/Cx30 channels exhibit distinct association with the actin network. Homomeric Cx30 interacts with β-actin in the perinexus of the gap junction plaque. Actin-depolymerizating drug disrupts Cx30 but not Cx26/Cx30 gap junction plaques.